High sensitivity of North Iceland (Tröllaskagi) debris-free glaciers to climatic change from the 'Little Ice Age' to the present. (August 2017) - Fernández-Fernández, José María; Andrés, Nuria; Sæmundsson, Þorsteinn; Brynjólfsson, Skafti; Palacios, David
The Tröllaskagi peninsula is located in northern Iceland, between meridian 19°30′W and 18°10′W, jutting out into the North Atlantic to latitude 66°12′N. The aim of this research is to study recent glacier changes in relation to climatic evolution of the Gljúfurárjökull and Tungnahryggsjökull debris-free valley glaciers in Tröllaskagi. Glacier extent mapping and spatial analysis operations were performed with ArcGIS (ESRI), using analysis of aerial photographs from 1946, 1985, 1994 and 2000, and a 2005 SPOT satellite image. The results show that these glaciers lost a quarter of their surface area between the 'Little Ice Age' and 2005. In this paper, the term 'Little Ice Age' follows Grove (2001) as the most recent period when glaciers extended globally between the medieval period and the early 20th century. The abrupt climatic transition of the early 20th century and the 25-year warm period 1925–1950 triggered the main retreat and volume loss of these glaciers since the end of the 'Little Ice Age'. Meanwhile, cooling during the 1960s, 1970s and 1980s altered the trend, with advances of the glacier snouts. Between the 'Little Ice Age' and the present day, the mean annual air temperature and mean ablation season air temperature increased by 1.9°C and 1.5°C, respectively, leading to a 40–50 m rise in the equilibrium line altitude (ELA) of the glaciers during this period. The response of these glaciers depends not only on the mean ablation season air temperature evolution but also on other factors such as winter precipitation. The models applied show a precipitation increase of up to more than 700 mm since the 'Little Ice Age'.